Knowledge Visualization of Students’ Performances: Antecedent of Knowledge Generation Model and Decision Making Model - Khamis, Shakiroh; Haji Ahmad, Azizah; D. Muraina, Ishola (International Journal of Engineering and Technology, 2018)
Visualization is critical to data analysis and has been used to portray intrinsic structure and pattern of data. However, there have been fewer study to visualize knowledge on the performance of student with respect to the internet and infrastructure provided by the institution of higher learning. The objective of this study is to propose a model that capable of visualizing knowledge on student’s performance in the institution of higher learning. The proposed model was developed through the integration of knowledge generation and decision making models. The model is believed to serve as a basis for analyzing and evaluation of services provided to the students by their respective institutions.